2021
DOI: 10.1111/hex.13319
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a structured short intervention against stigmatisation in chronic visible skin diseases: Results of a controlled trial in future educators

Abstract: Background Chronic visible skin diseases are highly prevalent, and patients affected frequently report feeling stigmatised. Interventions to reduce stigmatisation are rare. Objectives This study aimed to evaluate the effectiveness of a structured short intervention in reducing stigmatising attitudes towards psoriasis in future educators. Methods The intervention consisted of four components: (1) self‐reflection, (2) education on skin diseases, (3) contact between participants and a person with psoriasis and (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The findings of the current study are mostly in line with 2 studies that aimed to reduce external stigmatization of visible chronic skin diseases, but through in-person approaches ( 9 , 10 ). Furthermore, at least 1 of the 2 studies reported an inter-group difference for each subcategory for a certain study time-point.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The findings of the current study are mostly in line with 2 studies that aimed to reduce external stigmatization of visible chronic skin diseases, but through in-person approaches ( 9 , 10 ). Furthermore, at least 1 of the 2 studies reported an inter-group difference for each subcategory for a certain study time-point.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, at least 1 of the 2 studies reported an inter-group difference for each subcategory for a certain study time-point. An agreement was given regarding less Stereotype Endorsement in the IG post-intervention and at the follow-up compared with the CG ( 9 , 10 ). Furthermore, both studies found evidence for a reduction in the desire for Social Distance and less stigmatized Reported and Intended Behaviour between the measurement time-points in the IG.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations